PEMBINAAN MORAL OLEH GURU PENDIDIKAN KEWARGANEGARAAN TERHADAP DISIPLIN BELAJAR SISWA - Hasanah, Sitti Uswatun (LPPM IKIP PGRI Pontianak, 2012)
Teachers as coaches in the learning process is a very influential factor in educating their students to improve a very strategic in all aspects of life. None of the activities in life or in the learning process is inseparable from the moral. Given the moral guidence by the teacher of Citizenship Education students, then students will automatically know where a good attitude and behavior do notÂ to do.